2023
DOI: 10.1038/s41598-023-40345-9
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the risk of discrimination on psychological distress experienced by early wave infected and late wave infected COVID-19 survivors in Japan

Megumi Hazumi,
Mayumi Kataoka,
Kentaro Usuda
et al.

Abstract: The psychological distress experienced by coronavirus disease of 2019 (COVID-19) survivors after recovery from the illness is amplified by discrimination endured because of their infection status. However, the difference in the risk of facing discrimination and risk of experiencing psychological distress in the early and late waves of the COVID-19 pandemic remain unclear. This study aimed to investigate whether the risk of facing discrimination because of infection status was lower in the early or late waves a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Such faulting tendencies are particularly pronounced in societies that strongly emphasize collective norms [ 59 ]. Meanwhile, our findings indicate a substantial decline in stigma levels toward individuals infected during the latter half of 2021 compared to those infected in the early wave of the COVID-19 pandemic; this was consistent with prior research [ 60 , 61 ]. This decline in discriminatory behavior may be attributed to the accumulation of knowledge about COVID-19 over time and its dissemination among the general population, resulting in a less stigmatizing social environment [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such faulting tendencies are particularly pronounced in societies that strongly emphasize collective norms [ 59 ]. Meanwhile, our findings indicate a substantial decline in stigma levels toward individuals infected during the latter half of 2021 compared to those infected in the early wave of the COVID-19 pandemic; this was consistent with prior research [ 60 , 61 ]. This decline in discriminatory behavior may be attributed to the accumulation of knowledge about COVID-19 over time and its dissemination among the general population, resulting in a less stigmatizing social environment [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…For example, information-based strategies can be used to reduce negative attitudes and perceived stigma within communities [ 64 ]. The intervention for HIV-related stigma highlights the effectiveness of implementing anti-stigmatizing campaigns [ 60 ] utilizing unifying symbols such as the globally recognized red ribbon, and fostering community activities as effective measures [ 53 ]. The red ribbon is a powerful symbol of HIV/AIDS awareness, care, empathy, and support globally [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed that COVID-19-related discrimination on psychological distress was more severe among those infected in later phases. 30 While the interpretation of the adjusted OR of probable PTSD in Wave 6 requires careful consideration, our findings emphasize the importance of preventing social discrimination, not only in the initial phases of the pandemic but throughout the entire pandemic duration.…”
Section: Ptsd In Covid-19 Patients Following Sars-cov-2 Infection Aft...mentioning
confidence: 69%
“…23 Another study showed that COVID-19 patients experienced significantly more COVID-19-related discrimination compared to individuals not infected with the virus from the same region. 24 This discrimination was associated with persistent psychiatric symptoms after recovery from primary SARS-CoV-2 infection, such as mood symptoms, 25 sleep disturbance, 26,27 anxiety, 25,28 psychological distress, 29,30 and probable PTSD. [31][32][33] A previous study conducted exclusively in Columbia between October 2020 and April 2021 showed that social discrimination against COVID-19 patients resulted in odds ratios (OR) of approximately 2.5 or higher for probable PTSD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation